Functionalized fullerene materials (fullerol nanoparticles) reduce brain injuries during cerebral ischemia-reperfusion in rat - Mohammad Taghi Mohammadi (Islamic Azad University, 2016)
Aim: Oxidative stress plays a crucial role in the pathophysiology of ischemic stroke. Since water-soluble fullerene derivatives act as the potent scavenger of oxygen free radicals in biological systems, we aimed to investigate the possible protective effects of fullerol nanoparticles on brain infarction and edema in transient model of focal cerebral ischemia in rat. Materials & Methods: Experiment was performed by three groups of rats (each group; n=8): sham, control ischemia (IR) and ischemia treated rats with fullerol. Brain ischemia was induced by 90 min middle cerebral artery occlusion (MCAO) followed by 24 hours reperfusion. Treated rats received fullerol at dose of 1 mg/kg 30 min before induction of MCAO. The brains were processed for histochemical triphenyltetrazolium chloride (TTC) staining and quantitation of the ischemic infarct. Finally, the brain hemispheres were weighed as an index of brain edema. Results: MCAO induced brain infarction in large areas of cortex (261± 23 mm3) and subcortex (138± 23 mm3). Treatment with fullerol significantly reduced the infarct volume both in cortex and subcortex by 64.75% and 52.17%, respectively. Induction of MCAO significantly increased the weights of right hemispheres in IR group (0.77± 0.01 g) compared with sham rats (0.59± 0.01 g). Treatment with fullerol decreased the weights of ischemic hemispheres in IR treated group (0.69± 0.03 g) compared to IR non-treated rats. Conclusion: Our findings indicate that fullerol nanoparticles are able to reduce the ischemia-induced brain injury and edema possibly through their scavenging properties.